Environmental Sanitation and Hygiene on Waste Collector in TPA Piyungan Bantul Yogyakarta (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
A garbagemen involved directly with garbage, it causes a garbagemen have injuried oftenly when they do their duty. Based on center of worker trans department Jakarta, the injury case causes has 81.169. A garbagemen risk, highly to influence. This is a descriptive kualitative research, the subject are garbagemen who lived in TPA Piyungan and people who involved to manage TPA Piyungan, Bantul Yogyakarta. Research use observed method and In-Depth Interview method. Data analyzed as kualitative descriptive. Data collected by triangulasi source technique.The result that sanitation and hygienic environtment and how to keep the environtment clean, and to maintain the risk environment work on the garbageman area is deficient. The suitability between sanitation and hygiene environment on the garbagemen still need to improve. Financing is the problem of the garbagemen, hygiene environment on garbagemen work areaâ€™s very deficient, that things happened too for willingness and act to create a healthy environment.Â